Alcohol Addiction: A Molecular Biology Perspective - Ferraguti, Giampiero; Pascale, Esterina; Lucarelli, Marco (Current Medicinal Chemistry, 2015)
Alcohol misuse represents worldwide an important risk factor for death and disability. Excessive alcohol consumption is widely diffused in different ethnicities and alcohol use is part of the lifestyle of both young and old people. The genetic basis of alcohol dependence concerning ethanol metabolism and the pathways of reward circuits are well known. The role of genetic variants in the neurobiology of addiction as well as in response to medication in alcoholism therapy still represents an intriguing argument that needs to be deeply analyzed and explained. The molecular approach to the study of these aspects could be difficult because of the large number of genes and variations involved. Our work is intended to offer an overview of genes and variants involved in alcohol addiction and pharmacogenetics. Our aim is to delineate a molecular approach strategy to look at alcohol dependence from a genetic and applicative point of view. The indications provided in this work should be of help for those who wish to undertake a molecular study of this multifactorial disease.
Keywords: pharmacogenetics